National Health Service Bill (memorandum)
1946-05-24 1946 1940s 6 pages PRIVATE AND CONFIDENTIAL JT.S.I.C.&.W.C.F.C.10/1. TRADES UNION CONGRESS NATIONAL HEALTH SERVICE BILL GENERAL The General Council wholeheartedly supports the object of a comprehensive national health service available to everyone and free of charge to the patient. We regard the provisions of the National Health Service Bill as a distinct improvement upon the proposals contained in the original Coalition Government's White Paper, and consider that they provide a basis for the building up of a really worth-while health service. At the same time we consider that the service is capable of improvement in a number of respects and with that end in view we make the following recommendations. SCOPE We have always stressed the importance of ensuring that every member of the community is included in the service. The Bill, by getting rid of the anomalous provisions of the present N.H.I. Scheme under which large sections of the community are excluded from the limited medical treatment available under that Scheme is a great step forward. Whilst appreciating that the Bill allows a person to pay for private treatment if he so desires we stress that safeguards will be required. It will be essential to ensure that the general standard of treatment available under the public service is in no way inferior to that available to paying patients. Unless this condition is fulfilled, and recognised as fulfilled by those using the service, the service would be gravely jeopardised. It will be necessary to ensure also that there is no contracting out on the grounds of voluntary contributions to hospital contributory schemes and so on. Furthermore no financial advantage should accrue to a general practitioner who refers a patient for a second opinion. We attach special importance to the safeguards which will be needed in connection with provision of hospital accommodation. The Bill provides that special hospital accommodation can be made available on payment, and furthermore that specialists working in the service can make arrangements for treatment of their private patients in hospital. In view of the shortage of hospital accommodation, which is likely to continue for some time after the introduction of the service, it will be necessary to ensure that medical need is the only factor taken into account for admission to hospital. AIM OF SERVICE While Section 1 of the Bill imposes duties for securing both improvement in health and prevention of illness, the Bill is mainly concerned with treatment services. Prevention of illness is no less important, and in this connection due importance should be attached to the conditions under which the population live and work, housing nutrition, and so on. Widely expanded research work will also be necessary, and we regret the failure to incorporate any specific new proposals for this in the Bill. GENERAL MEDICAL PRACTICE There must be a sufficient supply of qualified practitioners to provide the service and it is our view that if the necessary action is not taken now, the service will be seriously affected. We strongly recommend that steps should be taken at once for 292/847/4/159